Adaptive Learning in Mathematics: A Case Study of Seventh-Grade Students - Huri Suhendri; Supardi Uki Sajiman; Nani Wartini; Ade Wintarsih; Enok Nia Kurniasih; Mega Juliana Soleh; Yudi Barnas Komaruddyi (Jurnal Inovasi Matematika, 2026)
This study aims to describe the implementation of adaptive learning in seventh-grade mathematics instruction at a public junior high school in Situraja, Sumedang Regency, and to analyze teachers’ roles in diagnosing students’ learning readiness, applying differentiated instruction, and providing feedback based on individual needs. This research employed a qualitative approach using a case study method. Research data were collected through classroom observations, interviews with teachers and students, and document analysis, including teaching modules, diagnostic assessment instruments, and student worksheets. The research instruments consisted of observation sheets, interview guides, and documentation guidelines. The findings indicate that adaptive learning was implemented through four main stages: initial diagnostic assessment to identify students’ learning readiness, student grouping based on readiness levels, differentiated learning activities using tiered tasks and collaborative work, and performance-based feedback focusing on conceptual understanding and improvement strategies. Teachers applied flexible grouping according to task complexity and students’ learning pace. Students’ responses to adaptive learning showed increased engagement, confidence, and understanding of mathematical concepts. These findings emphasize the importance of adaptive learning in accommodating diverse student learning characteristics at the junior high school level. This study offers a practical model of classroom-based adaptive learning applicable to schools with limited technological resources.